Balance and characteristics of job market and employment generation in Colombia 2002-2010 - Torres, Roberto Mauricio Sánchez (Universidad Pedagógica y Tecnológica de Colombia, 2013)
This article presents a balance regarding employment and job market in Colombia from 2002 to 2010. Due to its significance in the recent evolution of labor market, special focus is given to informal, independent, and selfemployment work. The research is focused on the analysis of information of labor market of the National Administrative Department of Statistics (DANE, for its acronym in Spanish), and based on the results, it is said that informality and independence are the main characteristics of the recent development of employment in Colombia.